The experiences of female immigrant hotel workers in the Icelandic labor market - Guðbjört Guðjónsdóttir 1979- (2010)
Iceland has received a growing number of immigrants over the last few years, which has largely been due to labor demand. Although migration and labor are structured by gender, research has lacked on the gendered experiences of immigrant workers in Iceland. This thesis seeks to give insight into the work experiences of immigrant women in Icelandic hotels. The main research questions I pose are: How do immigrant women experience the Icelandic labor market? How are labor market experiences shaped by gender and immigrant status? How is the hotel work organized and how are the women’s working conditions? The research was conducted from autumn 2007 to spring 2009. The study is based on qualitative and ethnographic methodology and the main methods used were interviews, participant observation and textual analysis. In the thesis I argue for the need of an intersectional approach when addressing labor market inequality. I demonstrate the importance of looking at how the women’s gender and status as immigrants intersect, when trying to account for their position in the labor market. The research shows the low status and often unfavorable working conditions that the women face and I point out the need for labor unions and state authorities to pay more attention to traditional “female” occupations. These are often positions that Icelanders have abandoned, and immigrants – especially women – have filled.